Pemodelan Aset 3D Interior Kamar Tidur Minimalis Dengan Penerapan Texturing PBR Untuk Meningkatkan Visualisasi Realistis - Sultan Alam Khalil; Riyadhul Fajri; Zulkifli Zulkifli (Fakultas Ilmu Komputer Universitas Almuslim, 2026)
Visualization quality is an important aspect in presenting interior design concepts realistically. Conventional texturing methods often produce flat and unrealistic appearances due to inaccurate light interaction. This study aims to implement Physically Based Rendering (PBR) techniques in modeling a minimalist bedroom interior using Blender software to improve visual realism. The development process follows the Multimedia Development Life Cycle (MDLC) method, which includes concept, design, material collecting, assembly, testing, and distribution stages. PBR materials are created by combining texture maps such as Albedo, Roughness, Metallic, and Normal through the Principled BSDF shader. The Cycles render engine is used to generate realistic lighting and shadows. The results show that PBR implementation significantly improves surface detail, light reflection accuracy, and overall realism compared to conventional texturing methods. This research proves that PBR-based texturing is effective for producing realistic interior visualizations for design presentation